Boundary-spanning marketing organization a theory and insights from 31 organization theories - Hult, G. Tomas M.; SpringerLink (Online service). (New York Springer, 2011)
Now more than ever, marketing is assuming a key boundary-spanning role: a role that also redefined the composition of the marketing organization. In this Brief, the marketing organization's integrative and mutually reinforcing components of marketing activities, customer value-creating processes, networks, and stakeholders are delineated within their boundary-spanning roles. Expanding upon his article published in the Journal of the Academy of Marketing Science in 2011, Tomas Hult draws thematic marketing insights from the integration of thirty-one organization theories to advance knowledge on the boundary-spanning marketing organization within four areas: strategic marketing resources, marketing leadership and decision making, network alliances and collaborations, and the domestic and global marketplace.
A Theory of the Boundary-Spanning Marketing Organization --Organization Theories Can Inform Research on the Marketing Organization -- Discussion, Insights, and Implications.
Electronic reproduction.
Keywords: Marketing -- Management; Electronic books